Hukum Menikahi Wanita Hamil Karena Zina Menurut Pandangan Imam Syafi’i dan Diimplimentasikan di Kantor Urusan Agama Tanjung Pura - Suaib Lubis; Muhammad Idrus (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
This study discusses the main problem, namely about how Imam Syafi'i thought about the law of marrying pregnant women because of adultery, and how the legal consequences arising from his thoughts. The method used in collecting data is library research, while the research data is doctrinal. The approach used is the ushul fiqh approach, which is to explain the opinions and arguments of Imam Syafi'i about the law of marrying pregnant women because of adultery. With the above method, it can be seen the reasons for Imam Shafi'i in his thinking about the law of marrying a pregnant woman because of adultery. Imam Shafi'i is of the opinion that a woman who becomes pregnant as a result of an extramarital relationship can be married by anyone. Be it by men who experienced it or by men who did not impregnate her. Imam Syafi'i argues that children resulting from adultery do not have musharah with their biological father. Regarding the issue of 'iddah, Imam Shafi'i is of the opinion that pregnant women due to extramarital relations do not have an 'iddah period. This is because the purpose of 'iddah is to respect the sperm or fetus contained in the woman (which is channeled through a legal relationship). While adultery is a relationship that is unlawful and illegitimate, therefore the sperm or fetus from the result of adultery is not obligatory to be respected. For this reason, Imam Shafi'i also argues that if women who are pregnant out of wedlock have performed a valid marriage contract, then they are allowed to have biological relations without having to wait for the birth of the baby they are carrying. Keywords: Law; Marrying a Pregnant Woman for Adultery; Imam Shafi'i's view